â€œAPLIKASI REDAYAKUâ€ SOLUSI INOVATIF MEDIA CYBERCOUNSELING PENANGANAN KEKERASAN SEKSUAL PADA ANAK - Saputra, Nur Mega Aris; Hotifah, Yuliati; Muslihati, Muslihati (KOPASTA : Jurnal Program Studi Bimbingan Konseling, 2021)
The high number of cases of sexual violence, especially in children, especially during the Covid-19 pandemic is very worrying. In addition, there is no special media to provide space for victims to tell stories or counseling. This research aims to develop the Redayaku application as a media for cyber-counseling in handling sexual violence in children which has theoretical and practical acceptability. The study used seven out of ten stages from the Brog and Gall development model to the test of potential users of counselors and students, which then carried out product revisions. At the data collection stage, a needs analysis was carried out by means of interviews with counselors and student victims of sexual violence which were taken using a purposive sampling technique based on the questionnaire scores on sexual violence. The test results from material experts, media experts and potential counselor users were analyzed using an inter-rater agreement with an index result of 1.00 which means very high. Whereas for the student user candidate test analyzed with a mean, it shows the interpretation results are very high on the usability aspect of 0.87; convenience of 0.86; accuracy of 0.88; and attractiveness of 0.92 Descriptive data of expert test habits and user tests are used as a reference in product improvement. So, Redayaku application as a cyber-counseling media and counselor's manual, theory and practice can contribute to handling violence in children.